Euro Plus Pact Adoption: Implications for Romanian Fiscal Policy; Adoptarea Pactului Euro Plus: Implicaţii asupra politicii fiscale a României - Daniel Dăianu; Ella Viktoria Kallai; Laurian Lungu (European Institute of Romania, 2012)
The current financial and economic crisis has highlighted the inadequacy of existing institutional and policy arrangements at the EU level. Even before this crisis, the EU economic growth was low, by international standards, revealing deep structural problems across EU countries, especially in the Southern flank. Macroeconomic imbalances have been building up, exposing a stratified EU with divergences in productivity and competitiveness, with rigidity of labour markets, impeding efficient market responses to shocks. The Monetary Union does not have adequate institutional arrangements, which may help it manage a major crisis, such as that of a last-call borrower, depreciation and burden-sharing mechanisms of asymmetric shocks, etc; various sui generis formulas are now being tested. Fiscal reactions vary depending on the level of the debts and on the speed these accumulate; at the same time, these are linked to the size of the budgetary expenditure and fiscal revenues as percentage in the GDP. The sooner the growth picks up, the more acceptable is the downsizing of the certain expenditure and/or the rise of some taxes, so that the ratio between the public debt and the GDP stabilizes (reduces, when it is the case).
Keywords: 330